Engineering the pathway in Escherichia coli for the synthesis of medium-chain-length polyhydroxyalkanoates consisting of both even- and odd-chain monomers - Qianqian Zhuang; Qingsheng Qi (Microbial Cell Factories, 2019)
Abstract Background Medium-chain-length polyhydroxyalkanoates (mcl-PHAs) containing various chain length monomers from C6 to C14 have more applications besides sustainable and environmental-friendly biomaterials owing to their superior physical and mechanical properties. We engineered a reversed fatty acid β-oxidation pathway in Escherichia coli that can synthesize mcl-PHA directly from glucose and achieved high yield. However, there were only even-chain monomers in the biosynthetic polymers. The need for mcl-PHA harboring both even- and odd-chain monomers with better and wider utility impels us to develop the biosynthetic routes for the production of the novel and unnatural mcl-PHA through rewiring the basic metabolism. Results In the present study, a propionate assimilation and metabolic route was integrated into the reversed fatty acid β-oxidation in order to produce mcl-PHA consisting of both even- and odd-numbered monomers. The content of odd-numbered monomers in mcl-PHA was improved with the increased propionate addition. After further deletion of pyruvate oxidase (PoxB) and pyruvate formate-lyase (PflB), the metabolically engineered chassis E. coli LZ08 harboring pQQ05 and pZQ06 (overexpression of prpP and prpE genes from Ralstonia eutropha H16) innovatively accumulated 6.23 wt% mcl-PHA containing odd-chain monomers ranging from 7 to 13 carbon atoms about 20.03 mol%. Conclusions This is the first successful report on production of mcl-PHA harboring both even- and odd-chain monomers (C6–C14) synthesized from glucose and propionate in recombinant E. coli. This present study achieved the highest yield of de novo production of mcl-PHA containing odd-numbered monomers in E. coli at shake-flask fermentation level. Continued engineering of host strains and pathway enzymes will ultimately lead to more economical production of odd-chain monomers based on market demand. The synthetic pathway can provide a promising platform for production of other value-added chemicals and biomaterials that use acetyl-CoA and propionyl-CoA as versatile precursors and can be extended to other microorganisms as intelligent cell factories.